(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this research stopping power was calculated theoretically by using Bohr and Bethe theories. Protons and Carbon stopping power were calculated in Cobait ,Lead by using Bragg’s Rule for compounds. The equations were programmed by using (MATLAB) language. The values of shell corrections, using kinetic theory of energy range (10-1000) MeV have been calculated. The calculations were compared with the practical results of the SRIM 2013 and there were some differences between practical and theoretical results .